Review of the Pathologic Characteristics in Myhre Syndrome: Gain-of-Function Pathogenic Variants in SMAD4 cause a Multisystem Fibroproliferative Response. (November 2022) - Starr, Lois J; Lindsay, Mark E; Perry, Deborah; Gheewalla, Gregory; VanderLaan, Paul A; Majid, Adnan; Strange, Charlie; Costea, George-Claudiu; Lungu, Adrian; Lin, Angela E
Background: Myhre syndrome, caused by pathogenic variants in SMAD4, is characterized by compact body habitus with short stature, distinctive craniofacial appearance, stiff skin, cardiovascular abnormalities (valve stenosis, coarctation, hypoplasia, or stenosis of aorta), effusions of potential spaces (pericardium, pleura, peritoneum), restricted movement of the joints (including thorax), and hearing loss. Lung and airway disease has been reported, but not always well-defined, to include interstitial lung disease, large airway obstruction, and pulmonary arterial hypertension. Excessive fibroproliferation of tissues especially following trauma or surgical instrumentation has been recognized, although these may also present spontaneously.Method: We report the pathologic features of 1 new patient with progressive choanal stenosis, and 22 literature cases, including the expanded history of 5 patients (3 who died).Results: Examination of patient tissues documents cellular fibroproliferation and deposition of excessive extracellular matrix explaining some of the observed clinical features of Myhre syndrome.Conclusion: Excessive fibrosis is noted in multiple tissues, especially heart, lung, and upper and lower airways. Our research provides the first systematic review to provide a knowledge base of gross and pathologic findings in Myhre syndrome.